WAHDATUL WUJUD DALAM DUA KEBUDAYAAN: KAJIAN ATAS SYAIR HAMZAH FANSURI DAN NASKAH USURRAN GANTI - Syukron, Benny Musta'an; Holil, Munawar (UNIVERSITAS PGRI YOGYAKARTA, 2025)
The Wahdatul Wujud doctrine brought by Hamzah Fansuri was once so dominant in Sufi discourse in Nusantara, as evidenced by the large number of manuscripts discussing it in various regions of the archipelago. This study utilizes two corpora with Wahdatul Wujud nuances and pantheistic characteristics from two different locations, the coast and the mountains, namely Hamzah Fansuri's Poems, edited by Drewes and Brekel (1986), and Usurran Ganti (UG), edited by Izuddin (2023). This study aims to analyze the similarities and differences in conveying the theological concept of Wahdatul Wujud and to analyze the various backgrounds that influence both texts in conveying this doctrine. The theory used is Roland Shaw's Syncretism (1994). The method employed in this study is an intertextual approach, comparing the analyzed corpus with other works by Hamzah Fansuri and various Islamic literature. The conclusion of this article is that both texts express the concept of Wahdatul Wujud in a pantheistic manner through natural symbols, albeit in different ways. Fansuri uses maritime metaphors that reflect the influence of Persian-Arabic Sufism, while the author of UG employs mountain symbols based on local cosmology. This difference stems from the authors' backgrounds; Hamzah Fansuri as an intellectual from a coastal region connected to the global Islamic network, while the author of UG blends Islam with pre-Islamic knowledge deeply rooted in the Uluan culture of South Sumatra. Fansuri also transforms non-Islamic symbols into Sufi allegories, while the UG author engages in cultural negotiation by replacing Islamic cosmological narratives with local cosmology. Fansuri's poetry symbolism is universal, whereas UG uses specific symbols tied to local beliefs.